HUBUNGAN PEMBERIAN REWARD AND PUNNISHMENT TERHADAP MINAT BELAJAR SISWA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS 4 DI SDN CILENDEK 2 KOTA BOGOR - Zein, Zeinia Tursina (Inspiratif Pendidikan, 2021)
Interest is a very important factor in student learning activities. To increase students interest in learning, there are many ways that a teacher can do, one of which is by using the Reward and Punnishment methods. This study aims to determine how much the relationship between reward and punishment towards students' interest in learning in Islamic religious education subjects. The method in this research uses a quantitative approach. This study took a sample of grade 4 SD with a population of 25 students. Data collection techniques in this study using questionnaires, interviews and documentation. The result of this research is that the correlation value between Variable X and Variable Y is 0.922. When viewed from the interpretation table, the correlation index obtained is between 0.90-1.00 which means there is a positive relationship between Variable X and Variable Y which is included in the correlation. or a very strong or very high relationship between the giving of Reward and Punnishment on Students Learning Interests in Islamic Religious Education Subjects. Then by looking at the table the value of r is N = 25. With the value of r-Table at the significance level of 5% = 0.396 and 1% = 0.505. So at a significance level of 5% = 0.922> r-Table 0.396 and 1% = 0.922> r-Table 0.505, it means that Ha is accepted and H0 is rejected. The data obtained showed that there was a significant relationship between the Giving of Rewards and Punnishment on Students Learning Interest in the 4th grade Islamic Religious Education subject at SDN Cilendek 2, Bogor City.